Transcribed ultraconserved region 339 promotes carcinogenesis by modulating tumor suppressor microRNAs. Issue 1 (December 2017) - Vannini, Ivan; Wise, Petra; Challagundla, Kishore; Plousiou, Meropi; Raffini, Mirco; Bandini, Erika; Fanini, Francesca; Paliaga, Giorgia; Crawford, Melissa; Ferracin, Manuela; Ivan, Cristina; Fabris, Linda; et al.
Abstract The transcribed ultraconserved regions (T-UCRs) encode long non-coding RNAs implicated in human carcinogenesis. Their mechanisms of action and the factors regulating their expression in cancers are poorly understood. Here we show that high expression ofuc.339 correlates with lower survival in 210 non-small cell lung cancer (NSCLC) patients. We provide evidence from cell lines and primary samples that TP53 directly regulatesuc.339 . We find that transcribeduc.339 is upregulated in archival NSCLC samples, functioning as a decoy RNA formiR-339-3p, -663b-3p, and-95-5p . As a result, Cyclin E2, a direct target of all these microRNAs is upregulated, promoting cancer growth and migration. Finally, we find that modulation ofuc.339 affects microRNA expression. However, overexpression or downregulation of these microRNAs causes no significant variations inuc.339 levels, suggesting a type of interaction foruc.339 that we call "entrapping". Our results support a key role foruc.339 in lung cancer. T-UCRs encode long non-coding RNAs implicated in human carcinogenesis, but the underlying mechanisms are poorly understood. Here, the authors identifyuc.339 as an oncogene in lung cancer that is upregulated through the loss of TP53 and promotes Cyclin E activation by entrapping regulatory miRNAs.